2015
DOI: 10.1681/asn.2014070639
|View full text |Cite
|
Sign up to set email alerts
|

Kelch-Like Protein 2 Mediates Angiotensin II–With No Lysine 3 Signaling in the Regulation of Vascular Tonus

Abstract: Recently, the kelch-like protein 3 (KLHL3)-Cullin3 complex was identified as an E3 ubiquitin ligase for with no lysine (WNK) kinases, and the impaired ubiquitination of WNK4 causes pseudohypoaldosteronism type II (PHAII), a hereditary hypertensive disease. However, the involvement of WNK kinase regulation by ubiquitination in situations other than PHAII has not been identified. Previously, we identified the WNK3-STE20/SPS1-related proline/alanine-rich kinase-Na/K/Cl cotransporter isoform 1 phosphorylation casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…We speculated that the inhibition of NKCC1-mediated GCl affects Ca 2+ transients following membrane depolarization in skeletal muscle cells similarly as seen in vascular smooth muscle cells1718. Thus, we analyzed the effect of bumetanide and furosemide on depolarization-evoked calcium transients after KCl treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the inhibition of NKCC1-mediated GCl affects Ca 2+ transients following membrane depolarization in skeletal muscle cells similarly as seen in vascular smooth muscle cells1718. Thus, we analyzed the effect of bumetanide and furosemide on depolarization-evoked calcium transients after KCl treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have focused on WNK signaling in extrarenal tissue and have found that WNK signaling also plays a role in other tissues, including vascular smooth muscle cells (9,26,38), the brain (39-41), neurons (42), the intestine (43), and the heart (44). However, the tissue distribution and intratissue localization of KLHL3 remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to KLHL3, KLHL2 directly interacts with WNK kinases, leading to their ubiquitination and degradation (45,46). Zeniya et al recently reported that ubiquitination by KLHL2 is the major regulator of WNK3 protein levels in response to angiotensin II stimulation, although other in vivo roles of KLHL2 were not determined (38).…”
Section: Discussionmentioning
confidence: 99%
“…WNKs are also regulated by binding Kelch-like adaptors, KLHL2 and KLHL3, which target them for degradation (12)(13)(14)(15)(16). Concentrations of WNKs can be changed relatively rapidly in cells by this type of degradative process with pathophysiological implications (70). Changing the WNK1 amount through degradation, distinct from changing WNK1 activity, may be a physiologically significant mechanism to induce autophagy.…”
Section: Discussionmentioning
confidence: 99%